On Complex Oscillation Property of Solutions for Higher-Order Periodic Differential Equations. (4th November 2007) - Chen, Zong-Xuan; Gao, Shi-An
Abstract : We investigate properties of the zeros of solutions for higher-order periodic differential equations, and prove that under certain hypotheses, the convergence exponent of zeros of the product of two linearly independent solutions is infinite.